Cassava Orange-Fleshed Sweetpotato Composite Gari: A Potential Source of Dietary Vitamin A - Atuna, Richard Atinpoore; Achaglinkame, Matthew Atongbiik; Accorley, Trudy Abla Sitsofe; Amagloh, Francis Kweku (Frontiers in Nutrition, 2021)
Gari, a fermented granular cassava food product, continues to play a major role in the diets of West Africans. The white cassava commonly used- for this product is devoid of provitamin A but may have a significant concentration of cyanogenic compounds. The physicochemical and functional properties of partial substitution of cassava with orange-fleshed sweetpotato (OFSP) to process gari were investigated. Two commonly consumed products “eba” and “soaked gari” were prepared from the various formulations and sensorially assessed. Cassava-OFSP composite gari (77% cassava : 23% OFSP; 75% cassava : 25% OFSP; and 73% cassava : 27% OFSP) did not significantly (p > 0.05) influence the moisture content (3.39-5.42%; p = 0.38); water absorption capacity (589 – 671 ml/g; p = 0.22); and swelling index (3.75 – 4.17; p = 0.08) compared with that of 100% cassava gari. Expectedly, increasing the levels of OFSP incorporation significantly (p < 0.001) resulted in color change from white (L*=83.99, a*=0.93, b*=16.35) to orange (L*=69.26, a*=7.74, b*=28.62). For β-carotene, the 73% cassava : 27% sample was about 5.2 times more than the level in 100% cassava gari. Also, it had lower residual cyanogenic compounds (0.37 vs. 1.71 mg/kg; p < 0.001, measured as hydrogen cyanide) compared with cassava-only gari. The sensory scores by the 100 panellists using a five-point hedonic scale (1-dislike extremely - 5-like extremely) exceeded the minimum threshold (3) for acceptance. Within the limits of this study, OFSP can be composited with cassava up to 27% to process gari that has similar physicochemical properties and sensorial preference as that of cassava-only. Further, the OFSP composited gari contains a significant amount of provitamin A and have a reduced residual cyanogenic compound. Thus, the composited gari could play a significant role in addressing vitamin A deficiency in Ghana than 100% cassava only.